The Effect of Yoga Practice on Labor Pain: A Systematic Review and Meta-Analysis - Maryam Nikpour; Mahdi Sepidarkish; Elham Joneidi; Mahbobeh Darzipour; Mojgan Firouzbakht (Wolters Kluwer Medknow Publications, 2024)
Background: Labor pain management is a critical aspect of midwifery care and an essential purpose of childbirth-related care. There is a need for comprehensive results on relevant non-therapeutic methods of reducing labor pain. This systematic review and meta-analysis study was conducted to investigate the effect of yoga practice on labor pain. Material and Methods: We performed a systematic literature search from SCOPUS, PubMed, Web of Science, and Science Direct for relevant studies from January 1, 1990 to June 2, 2022. We selected published quasi-randomized and randomized controlled trial studies that evaluated the effect of yoga practice on labor pain. Quality research was applied. We pooled the Standardized Mean Dfference (SMD) of labor pain in pregnant women with and without yoga practice during pregnancy using a random-effects model at 95% Confidence Intervals (CIs). Results: Nine studies including 660 women were included in the meta-analysis. Pregnant women in the yoga practice group experienced statistically significantly low labor pain at the beginning of the active phase compared to the control group (SMD: -1.10, 95% CI: -1.61, -0.58, p < 0.001; I2 = 89%). Yoga interventions also reduced the intensity of labor pain in active (SMD: -1.32, 95% CI: -2.03, -0.60, p < 0.001; I2 = 92%) and transition (SMD: -1.93, 95% CI: -2.87, -0.99, p < 0.001; I2 = 92%) phases compared to the control group, respectively. Conclusions: The results of the study showed that yoga practice during pregnancy reduces the intensity of labor pain in different labor phases. However, these findings should be considered cautiously due to the substantial heterogeneity between studies.